Clinical profile of patients with chronic headache in a tertiary care hospital - C., Senthil; N., Gunasekaran (International Journal of Advances in Medicine, 2016)
Background: Headache is one of the most common maladies which affect humans. However, headache has no been sufficiently studied as a cause of morbidity in the developing world. The present study was conducted to study the etiological and clinical profile of chronic headache patients using the second edition of International Classification of Headache Disorders (ICHD-2), in a tertiary care referral centre. Methods: The study included 100 patients with complaints of headache for more than 3 months attending the outpatient department of Government Royapettah hospital, Chennai, Tamil Nadu, India. Patients underwent thorough clinical examination and psychiatric evaluation and clinical investigations were done as and when required. Results: Among the 100 patients with chronic headache, chronic primary headache (82%) was the most common type, with migraine found in 49% of cases, and tension-type headache (TTH) in 23%. Among the secondary types, the most common was headache caused by overuse of analgesics and post sinusitis. Chronic headaches were significantly more common in women and younger age groups. Conclusions: Since more than 90% of headaches seen in practice are primary headaches, it is to be realised that matters have come a long way in the last decade and these is now enough evidence to prove that primary headaches are a genuine potentially treatable biological problem. This study would help in identifying the significant gaps in headache care and in strengthening existing health systems so that they better recognize headache disorders.